Mechanical and morphological properties of rice husk-filled polypropylene composities with struktol compatibiliser - Mohd Aridi, Nor Atirah (2016)
Development of new bio-based composites from renewable resources is getting wide attention from researchers due to environmental issue caused by traditional composites. Rice husk is a new potential renewable source of fillers for bio-composites to produce green products. Rice husk is the outer sheath surrounding rice grains during their growth. The aim of this work is to systematically review the parameters that affect the rice husk –polymeric composites in order to enhance their usage in various sustainable designs and applications. The main objectives of the work are to investigate the effect of filler loading on mechanical properties rice husk polypropylene composites and the effect morphological and performance deterioration of rice husk-polypropylene composites due to various liquid uptakes. Basically the main problem statement is to achieve a good combination of properties and processability at a moderate cost. Therefore, more efficient utilization of rice husk is urgently needed. One of the efforts is to produce value-added products such as rice husk polymer composites from these important bio-resources, several factors that influence and affects the properties of the composites need to be considered. Thus the optimum formulation of the polymer composite will be investigated. The combination of hydrophilic rice husk and hydrophobic polypropylene was caused poor interfacial bonding between fibre and matrix. Thus, additive agent struktol is used to improve the bonding between fibre and matrix. Five levels of filler loading (35, 40, 45, 50 and 55 wt%) were designed. All of the tensile strength, Young’s modulus, Flexural strength, flexural modulus and impact strength properties were carried out. The results showed that 50 wt% filler-loaded composites had optimum tensile strength, flexural strength and flexural modulus whereas the 35 wt% of filler loading case was the best regarding Young’s modulus, flexural strength, flexural modulus and impact strength. Furthermore, the scanning electron microscope results demonstrate that as filler loading increases, more voids and fiber pull-out occur.